Analisis Likuiditas, Profitabilitas, Kebijakan Hutang Terhadap Nilai Perusahaan Yang Terdaftar Di BEI - Eliza, Tony Sudirgo (Jurnal Paradigma Akuntansi, 2019)
The objectives of this research to liquidity (CR), profitability (ROA), and debt policy (DER) on firm value (PBV) both partially and simultaneously for property, real estate and building construction companies listed on the Indonesia Stock Exchange in 2015-2017. The sample of the company under study was selected using a purposive sampling technique and produced a total of 40 companies. This research was conducted using multiple regression analysis and Eviews 9.0 software. The results showed that liquidity partially had a negative and not significant effect on firm value, while profitability and debt policy partially had a positive and significant influence on firm value. The results of the study show that liquidity, profitability, and debt policy simultaneously have a significant effect on firm value